Comparative appraisal of nutrient recovery, bio-crude, and bio-hydrogen production using Coelestrella sp. in a closed-loop biorefinery - Kopperi, Harishankar; Mohan, S. Venkata (Frontiers in Bioengineering and Biotechnology, 2022)
Algal-biorefinery was designed in closed loop by three stage integration of diary wastewater (DWW) treatment, Hydrothermal Liquefaction (HTL) of defatted algal biomass and acidogenic process in a semi-synthetic framework. Initially, Coelestrella sp SVMIICT5 was grown in 5 L photo-bioreactor and scaled up in 50 L flat-panel photo-bioreactor using DWW. The microalgal growth depicted higher photosynthetic efficiency resulting in biomass growth of 3.2 g/L of DCW with 87% treatment efficiency. The biomolecular composition showed 26% of lipids with good fatty acids profile (C12-C21) as well as with carbohydrates (24.9%) and protein (31.8%) content. In the second stage, de-oiled algal biomass was valorized via HTL process at diverse temperatures (150oC, 200oC and 250oC) and reaction atmospheres (N2 and H2) wherein 250oC (H2) condition resulted 52% biocrude fraction having HHV of~29.47 MJ/kg (bio-oil) with saturated hydrocarbon content of 64.3%, that can be further upgraded to aviation/jet fuels. The energy recovery (73.01 %) and elemental enrichment (carbon; 65.67 %) was relatively greater in H2 than N2 conditions. Finally, complex structured HTL-AF stream was subjected to dark-fermentation and it resulted in total bio-H2 production of 231 mL/g of TOC with 63% of treatment efficiency. Furthermore, the life cycle analysis (LCA) was performed for mid-point and damage categories to study the sustainability of the integrated process. Thus, the study depicted comprehensive wastewater treatment and valorization of de-oiled algal biomass for chemical/fuel intermediates in biorefinery context.